Antecedents of Purchase Decision of Vape Users in Samarinda - Diah, Ahyar M.; Surahman, Surahman; Azizah, Amiril; Setiawan, Indra; Kintani, Aninda; Inggrid, Queen (International Journal Labs, 2023)
Background: Vape, sometimes known as